ICE handbook of geosynthetic engineering : geosynthetics and their applications - Shukla, Sanjay Kumar (ICE Publishing, 2022)
This is a text to which students (at all levels) and engineers in search of novel approaches to solutions for civil engineering problems can refer. The topics presented are based on major field application areas for geosynthetics in civil engineering.